2010
DOI: 10.1007/s11596-010-0665-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left atrial function in diabetes mellitus by left atrial volume tracking method

Abstract: The value of the left atrial volume tracking (LAVT) method in the evaluation of left atrial (LA) function in patients with diabetes mellitus (DM) was examined in this study. Fifty-eight DM patients as DM group and 40 healthy people as normal control group were enrolled in this study. EUB-6500 echocardiographic imaging system with LAVT was applied to display and analyze the LA volume curve imaging on LV apical two and four chamber views. The maximal LA volume at end-systole (LAV(max)), LA volume at the onset of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 26 publications
5
20
0
2
Order By: Relevance
“…Earlier studies based on LA phasic volume assessment and tissue Doppler derived strain rate imaging demonstrated impairment in LA reservoir and conduit function in diabetes, occurring in association with increased LV mass, abnormal LV geometry and LV diastolic dysfunction with an associated increase in LA contractile function (58)(59)(60)(61). In a recent study comparing 73 type 2 diabetic patients to age and gender matched normal controls Kadappu et al demonstrated larger indexed LA volumes in diabetics, independent of the effect of hypertension and diastolic dysfunction.…”
Section: Diabetes Mellitusmentioning
confidence: 96%
“…Earlier studies based on LA phasic volume assessment and tissue Doppler derived strain rate imaging demonstrated impairment in LA reservoir and conduit function in diabetes, occurring in association with increased LV mass, abnormal LV geometry and LV diastolic dysfunction with an associated increase in LA contractile function (58)(59)(60)(61). In a recent study comparing 73 type 2 diabetic patients to age and gender matched normal controls Kadappu et al demonstrated larger indexed LA volumes in diabetics, independent of the effect of hypertension and diastolic dysfunction.…”
Section: Diabetes Mellitusmentioning
confidence: 96%
“…The available data indicate the impairment of left atrial (LA) function in diabetic patients [6][7][8][9][10], whereas information about right atrial (RA) function in this population is still missing. The assessment of atrial function is clinically important because atria are not only reservoirs, but also active contractile chambers that have the ability of ventricular filling during ventricular diastole.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we demonstrated that indexed LA volumes and AEV, TEV increase significantly in preDM even which is mainly due to BMI and preDM and BMI was the only factor that had significant effect on LA functions. Assessment of LA volumes and functions is a growing interest since changes in LA size and functions are associated with CVE such as atrial fibrillation, stroke, diastolic dysfunction and LV failure in general and diabetic population [9][10][11][12][13][14][15][16][17]. 2D echocardiography derived LA volume provides more accurate assessment of LA size because of the irregular geometry of LA as it often enlarges asymmetrically, resulting in variable shape that may underestimate LA size [6].…”
Section: Discussionmentioning
confidence: 99%
“…Indexed V max <29 ml/m 2 and indexed LA diameter <24 mm/m 2 for both sexes were defined as normal LA volume and LA diameter for 2D-echocardiographic evaluation [22]. Impairment of LA functions in patients with DM was demonstrated in previous studies by using 2D, 3D echocardiography, myocardial strain imaging, and CMRI.6 [16,17,[23][24][25]. Moreover, Kadappu et al reported that LA dilatation in DM was independent of associated hypertension and diastolic dysfunction which was called atrial cardiomyopathy [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation